2016
DOI: 10.2197/ipsjjip.24.20
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire Testing: Identifying Twitter User's Information Sharing Behavior during Disasters

Abstract: The use of Twitter by citizens during catastrophic events is increasing with the availability of Internet services and the use of smartphones during disasters. After the Great East Japan Earthquake on 2011, Twitter was flooded with lots of disaster information, including misinformation that have been widely spread by retweet. Accordingly, we developed a questionnaire to investigate factors influenced people decision making to retweet disaster information they read from Twitter in disaster situations. We develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recent work has also applied retweeting motivations in specific contexts. For example, during disaster situations, users usually retweet to share information, to convey the significance of information in their network, to express their feelings, or to get feedback/alert other people[ 22 ]. A conceptualization and assessment of retweeting motivations can offer valuable extensions to the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has also applied retweeting motivations in specific contexts. For example, during disaster situations, users usually retweet to share information, to convey the significance of information in their network, to express their feelings, or to get feedback/alert other people[ 22 ]. A conceptualization and assessment of retweeting motivations can offer valuable extensions to the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…This dataset contains 333 URLs, accounting for 0.73% of the unique URLs. Previous studies have shown, the use of the retweet count (used in the ‘most retweeted tweets’ dataset) can be an indication of tweets that the most users express: the significance of information to their followers, feelings and/or get feedback/alert others [ 68 , 69 ]. Retweets are used rather than likes in this paper as the focus is on the circulation of information, hence they are an important aspect of the social media information ecology [ 11 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data from the second stage is then used as input in the third activity of P3, namely PLS-SEM analysis which produces statistical information about the test indicators, reliability and validity [45][46][47][48][49]. Stage P4 conducts interpretative analysis activities that produce important justifications related to testing the questionnaire [50][51][52]. Stage P5 is a questionnaire renewal activity to get a better questionnaire than the previous questionnaire [53].…”
Section: Figure 2 Stages Of Researchmentioning
confidence: 99%